EFFECTS OF REGULARLY ARRAYED ROUGHNESS ON FLOW RESISTANCE AND TURBULENT FLOW STRUCTURE IN AN OPEN CHANNEL - Sukarno, . (Sam Ratulangi University, 2014)
Effects of regularly arrayed cylindrical and sphere roughness on flow resistance and turbulent characteristics in an open channel have been investigated over a completely rough-bed with uniform stainless steel rods and glass beads. Detailed spatial measurements of streamwise and vertical velocity fluctuations were conducted using Particle Image Velocimetry in a vertical plane along the completely rough bed surface. Experimental results indicated that flow resistance with sphere roughness is higher than that with cylindrical roughness and significant degrees of spatially regular variation in the time-averaged velocities were generated along the rough elements in case of the large ratio of the roughness height to flow depth. In addition, Reynolds shear stress and turbulent intensity abruptly decreased near the ridge of roughness elements. It was suggested that the difference in flow resistance between cylindrical roughness and sphere one, these organized flow structure were explained by form induced stress.Keywords: open-channel shallow flow, flow resistance, rough bed, turbulent characteristics, PIV.